Analisis Minat Belajar Siswa Mata Pelajaran IPA di Kelas 5 SD Muhammadiyah 02 Medan - Ziana Zahra Fadilah; Putri Viona; Indah Pratiwi (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Interest in learning is a very important factor in the success of learning. This study aims to analyze and describe the learning interests of class V-B students at SD Muhammadiyah 02 Medan. This research uses a qualitative-descriptive method. The subjects of this study were students of class V-B which consisted of 29 students to serve as informants. Data collection techniques using a questionnaire. The research was conducted by giving questionnaires to students to find out students' interest in learning science. Based on the results of the study it can be concluded that interest in learning in this study is in the high category, interest in learning is measured using four indicators that are used as measurements, namely students' feelings of pleasure, student interest, student attention, and student involvement. Interest in learning has a positive effect on the results of the percentage of student learning outcomes. Thus an increase in learning interest will also increase student learning outcomes. Minat belajar merupakan faktor yang sangat penting dalam keberhasilan belajar. Penelitian ini bertujuan untuk menganalisis dan mendeskrispsikan minat belajar siswa kelas V-B SD Muhammadiyah 02 medan.Penelitian ini menggunakan metode kualitatif-deskriptif. Subjek penelitian ini adalah siswa kelas V-B yang terdiri dari 29 siswa untuk dijadikan sebagai informan. Teknik pengumpulan data menggunakan angket. Penelitian dilakukan dengan memberikan lembar angket kepada siswa untuk mengetahui minat belajar siswa terhadap pelajran IPA. Berdasarkan hasil penelitian dapat disimpulkan bahwa minat belajar dalam penelitian ini berada pada kategori tinggi, minat belajar tersebut diukur menggunakan empat indikator yang dijadikan ukuran yaitu perasaan senang siswa, ketertarikan siswa, perhatian siswa, dan keterlibatan siswa. Minat belajar berpengaruh positif terhadap hasil persentase hasil belajar siswa. Dengan demikian adanya peningkatan minat belajar maka akan naik pula hasil belajar siswa.